Surface-selective direct 17O DNP NMR of CeO2 nanoparticles - Hope, Michael A.; Halat, David M.; Magusin, Pieter C.M.M.; Paul, Subhradip; Peng, Luming; Grey, Clare P. (Royal Society of Chemistry, 2017)
Surface-selective direct 17O DNP has been demonstrated for the first time on CeO2 nanoparticles, for which the first three layers can be distinguished with high selectivity. Polarisation build-up curves show that the polarisation of the (sub-)surface sites builds up faster than the bulk, accounting for the remarkable surface selectivity.